COVID-19 presenting as acute pericarditis. Issue 1 (21st January 2022) - Ghosh, Soumitra; Panda, Prashant; Sharma, Yash Paul; Handa, Neha
Abstract : COVID 19, caused by SARS-CoV-2, is a highly infectious disease, mainly affects the respiratory system. In this article, we have presented a case of COVID-19, who presented solely with pericarditis without myocarditis, without any respiratory symptoms. The diagnosis was made based on clinical, electrocardiographic, radiological and biological findings. He was treated successfully with aspirin and colchicine. Our case highlights an atypical presentation of COVID-19, which should be kept in mind in the present pandemic and to diagnose and isolate early to limit the spread of infection.